PENYIDIKAN TERHADAP TINDAK PIDANA PELANGGARAN WARNET YANG TIDAK MEMILIKI IZINPERATURAN DAERAH KOTA PEKANBARU NOMOR 6 TAHUN 2015 TENTANG PENATAAN DAN PENGELOLAAN PENYELENGGARAAN MENARA TELEKOMUNIKASI . - Vaternus Irwanto Gultom; Mexsasai Indra; Ferawati ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
The development of Computer Technology, telecommunication, andinformation has been running in such a way that at this time has been very muchdifferent from previous years. The increasing growth of business activities in thetelecommunication sector makes the government need to do structuring andcontrolling for the realization of postal and telecommunication services thatquality, efficient and positive impact for the community. Based on Article 1 point44 of Pekanbaru City Regulation No. 6 of 2015 on the Management andArrangement of the Telecommunication Tower Operation. Based on theobservations, the authors found several cafes that do not have permission. Basedon the above background, the authors are interested to examine this issue with thetitle